1993
DOI: 10.1111/j.1365-2109.1993.tb00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of a hillstream catfish, Glyptothorax madraspatanum (Day), from the Garhwal, Central Himalaya, India

Abstract: This paper studies maturity and spawning tendency of a hillstream catfish, Clyptothorax madraspatanum (Day), in the Western Nayar River, Garbwat. Central Himalaya, India. The fish is a protracted spawner as it spawns only once during the limited period from July to August. Fecundity ranges from 1640 to 6830 eggs and is more closely related to ovary weight and fish weight than ovary and fish length. There was a non-significant sex ratio of 1:1-24 between males and females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…The present study indicate that the fish Botia dayi Hora spawn for a limited period (August-September) with a single batch of development eggs showing a single spawning frequency. On the other hand some species have a prolong breeding period as Tor chelynoides (Uniyal, et al, 2004) or they spawn twice a year as S. plagiostomus of the river Pinder (Bisht,1985) and B.bendelisis of river Nayar (Dobriyal and Singh, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study indicate that the fish Botia dayi Hora spawn for a limited period (August-September) with a single batch of development eggs showing a single spawning frequency. On the other hand some species have a prolong breeding period as Tor chelynoides (Uniyal, et al, 2004) or they spawn twice a year as S. plagiostomus of the river Pinder (Bisht,1985) and B.bendelisis of river Nayar (Dobriyal and Singh, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies conducted on hill stream fishes indicated that Glyptothorax pectinopterus mature at a size of 125 mm (male) and 121 mm (female) as reported by Dobriyal and Singh (1989). Dobriyal and Singh (1987) reported size at first maturity for Barillius bendelisis as 83 mm (female ) and 104 mm (male). Uniyal, et al (2004) reported 96 mm and 148 mm for male and female T. chelynoides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plenty of research work has been done on the food and feeding habits of freshwater fishes. Some of the significant contributors in these types of researches are Pillay (1953), Sharma (1984), Dobriyal and Negi (1998), Thapliyal et al, (2004), Mondal et al, (2005 and Sharma et al, (2018). The aim of the study was to investigate the type of food eaten by Puntius conchonius.…”
Section: Introductionmentioning
confidence: 99%
“…It would be advantageous for hatchery managers to extend the spawning season of cultivated fish that do not spawn naturally in confinement. Circannual endogenous rhythms of recrudescence and regression of the ovaries have been reported in a number of catfish species including Heteropneustes fossilis (Sundararaj & Vasal 1976), Clarias gariepinus (Van Den Hurk, Viveen, Pinkas & Van Oordt 1985; Van Oordt, Peute, Van Den Hurk & Viveen 1987), Glyptothorax madraspatanum (Dobriyal & Singh 1993), Mystus nemurus (Khan, Ambak, Ang & Moshin 1990) and C. macrocephalus (Carreon, Ventura & Almazan 1973). Experiments have shown that environmental factors such as photoperiod, temperature, rainfall, food availability or the presence of conspecifics play a determining role in the regulation of internal rhythms in reproduction (Sundararaj & Vasal 1976; Van Weerd, Sukkel & Richter 1988).…”
Section: Introductionmentioning
confidence: 99%